Hubungan Jumlah Cluster of Differentiation 4 (CD4) dengan Infeksi Oportunistik Pada Pasien HIV/AIDS di Rumah Sakit Umum Daerah (RSUD) DOK II Jayapura - Mirna Widiyanti; Hotma Hutapea (Jurnal Biologi Papua, 2015)
Human Immunodeficiency Virus (HIV) is an infection that attacks and weakens the immune system. HIV infection causes a decrease in the number of Cluster Differentiation 4 (CD4) thereby increasing the progression of the disease and lead to high risk of opportunistic infections (OI). The purpose of this study was to examine the relationship between CD4 cell count with opportunistic infections in patients infected with HIV/AIDS. Analytical research methods using cross-sectional design, by taking medical records. The population in this study were 67 patients with HIV/AIDS in the VCT Clinic Dok II Hospital Jayapura 2014. Data were processed with the Chi Square test hypotheses. Based on the results of hypothesis testing of 67 patients, there were 21 people have opportunistic infections. Tuberculosis is an opportunistic infection that is most common (17.9%). Significance of the relationship seen in the low CD4 counts (< 350 cells/mm3) and found value of 0.02 (CI 95%) which indicates that there is a relationship if p<0.05. Conclusion: there is a relationship between CD4 cell count with opportunistic infections.Key words: CD4, opportunistic infection, HIV/AIDS, hospital.